Role of caregiver-reported outcomes in identification of children with prenatal alcohol exposure during the first year of life. (September 2018) - Bakhireva, Ludmila; Lowe, Jean; Garrison, Laura; Cano, Sandra; Leyva, Yuridia; Qeadan, Fares; Stephen, Julia
Abstract Background Earlier identification of children with prenatal alcohol exposure (PAE) remains a challenge. The objective of this study was to identify neurobehavioral (NB) outcomes associated with PAE in infants. Methods This manuscript evaluates NB outcomes at 6.33±1.12 months of age in 93 infants (39 PAE and 54 No-PAE) recruited prospectively into the ENRICH cohort. PAE was assessed by prospective repeated TLFB interviews and a panel of ethanol biomarkers. NB outcomes were evaluated by the Bayley Scales of Infant Development (BSID-III), Parenting Stress Index (PSI), Infant Behavior Questionnaire (IBQ-R), and Infant Sensory Profile (ISP). Results Mean maternal age at enrollment was 28.18±5.75, and 64.52% were Hispanic/Latina. Across three TLFB calendars, absolute alcohol per day in the PAE group was 0.44±0.72, corresponding to low-moderate alcohol consumption. While no association was observed between PAE and BSID-III (P 's>0.05), PAE was associated with higher scores on the PSI difficult child scale ( =13.9;P =0.015), total stress ( =13.9;P =0.010), and IBQ negative affect ( =8.60;P =0.008) measures after adjustment for covariates. Conclusions Caregiver-reported assessments may provide a currently unrecognized opportunity to identify behavioral deficits, point to early interventions, and should be included in clinical assessments of infants at-risk for fetal alcohol spectrum disorder.